2011
DOI: 10.1128/jvi.00558-11
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated or Live-Attenuated Bivalent Vaccines That Confer Protection against Rabies and Ebola Viruses

Abstract: The search for a safe and efficacious vaccine for Ebola virus continues, as no current vaccine candidate is nearing licensure. We have developed (i) replication-competent, (ii) replication-deficient, and (iii) chemically inactivated rabies virus (RABV) vaccines expressing Zaire Ebola virus (ZEBOV) glycoprotein (GP) by a reverse genetics system based on the SAD B19 RABV wildlife vaccine. ZEBOV GP is efficiently expressed by these vaccine candidates and is incorporated into virions. The vaccine candidates were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(113 citation statements)
references
References 49 publications
1
111
0
1
Order By: Relevance
“…The vaccine candidates were avirulent in adult mice and displayed low neurovirulence in suckling mice. Another study also demonstrated that 5 £ 10 5 FFU of this vaccine could induce humoral immunity and conferred protection from both RABV and EBOV after intraperitoneal challenging with 1000 PFU of mouse-adapted EBOV in mice 68 (Table 3). In 2013, a study immunized NHPs with a platform based on replication competent RABV, replicationdeficient RABV, or chemically inactivated RABV expressing EBOV GP.…”
Section: Rvsv-ebovmentioning
confidence: 92%
“…The vaccine candidates were avirulent in adult mice and displayed low neurovirulence in suckling mice. Another study also demonstrated that 5 £ 10 5 FFU of this vaccine could induce humoral immunity and conferred protection from both RABV and EBOV after intraperitoneal challenging with 1000 PFU of mouse-adapted EBOV in mice 68 (Table 3). In 2013, a study immunized NHPs with a platform based on replication competent RABV, replicationdeficient RABV, or chemically inactivated RABV expressing EBOV GP.…”
Section: Rvsv-ebovmentioning
confidence: 92%
“…The vaccine candidates were shown to be avirulent in adult mice and displayed low neurovirulence in suckling mice [70]. These vaccines also could induce humoral immunity and conferred protection from both RABV and EBOV lethal challenge in mice [71]. Furthermore, pre-existing immunity against RABV did not impact the immunogenicity of these vaccines in mice [72].…”
Section: Recombinant Rabies Virus (Rabv)-based Vaccinesmentioning
confidence: 95%
“…Full-length genomic cDNA constructs were based on the pcBNSP-333 backbone described previously (24,60). The open reading frames from the CDV F and H genes were cloned from plasmids pCG-Fos, pCG-F5804P, pCG-Hos, and pCG-H5804P (59) while inserting 5= BsiWI and 3= NheI restriction sites (Fig.…”
Section: Methodsmentioning
confidence: 99%